Evaluation of Hepatitis A and Isolated Anti-Hbc IgG Prevalences in A City of Eastern Anatolia - Cavus, Bilger; Alagoz, Mehmet; Gurkan, Yakup (Archives of Clinical and Biomedical Research, 2018)
Background: Hepatitis A and hepatitis B are virological diseases which cause serious health problems worldwide and are closely related with social, economic, and cultural status of countries. Their seroprevalences change with varying social conditions. The purpose of our study was to evaluate hepatitis A and B encounter rates and anti-HAV IgG and Hbc IgG serological parameters in patients admitted to our clinic. Method: Biochemical tests of the patients included in our study were studied using Mindray BS2000M autoanalyzer and Mindray kits in accordance with the instruction manual of the producer company. ELISA tests (HbsAg, anti- Hbs, anti Hbc IgG, and anti HAV IgG) were studied using Cobas 6000 e601 autoanalyzer and Roche kits with the chemiluminescence method in accordance with the instruction manual of the producer company. Results: This study included 897 subjects (475 females and 422 males) who admitted to a gastroenterology clinic of our hospital for various reasons and had hepatitis viral parameters testing. In 874 study participants (97.4%) anti HAV IgG was positive. HAV IgG was positive in 465 of the 475 females (97.9%) and 409 of the 422 males (96.9%). There was not a statistically significant difference in anti HAV IgG positivity according to sex (p=0.402). Isolated anti Hbc IgG positivity rate was 3.7%. Isolated anti HbcIgG positivity rate was 3.2% in females (s=15) and 4.3% in males (s=18). Conclusion: Anti-HAV IgG positivity rate in our study was 97.4%. Isolated anti Hbc IgG positivity rate was 3.7%. Both hepatitis A and hepatitis B encounter rates were detected to increase with age. High anti-HAVIgG positivity in our society warrants careful reviewing of our food and water resources. Moreover, informing public about contagiousness of hepatitis and implementing vaccination programs in a controlled fashion ar